Electromagnetic hypersensitivity-a COMAR technical information statement. - Ziskin, M.C.
Certain individuals experience a variety of health symptoms, which they attribute to exposure to electric or magnetic fields from sources such as power lines, household appliances, visual display units (VDUs), light sources, mobile telephones and mobile phone base stations. Some individuals are so severely afflicted that they cease work and change their entire lifestyle, or take exceptional measures such as sleeping under aluminium blankets. This perceived sensitivity to electromagnetic fields has the general name "electromagnetic hypersensitivity" or EHS. The fields that electromagnetically hypersensitive individuals consider to be the cause of their symptoms vary considerably, but they are invariably far below recommended exposure limits, and very far below field levels that are known to produce adverse effects in unaffected humans. This Technical Information Statement describes what is known about EHS and summarizes recommendations from medical groups for helping people with EHS.
Keywords: COMAR technical information statement; Technical Information Statement; Adverse effects; Electromagnetic hypersensitivity; Household appliances; Lifestyle changes; Light sources; Mobile phone base stations; Mobile telephones; Power lines; Sleeping under aluminium blankets; Unaffected humans; Visual display units